Non-invasive nanosensor monitoring of mRNA expression for regenerative medicine application - Wiraja, Christian (2017)
The field of regenerative medicine focuses on utilizing therapeutic cells either on itself or in conjunction with scaffolds to replace, repair or allow regeneration of injured tissues. Thus far, various approaches involving wide ranges of cell and biomaterial types have been proposed and validated at the bench-side (laboratory). However, their translation towards the clinical side have been minimal, with most approaches failing in pre- or early clinical trial phase. One limiting factor that is very crucial in ensuring successful treatment efficacy and thus translation process is quality control of cells to be injected/implanted. Prior to its re-introduction, cells of various sources need to be validated for their functionality (i.e. phenotype). Conventionally, such verification is achieved through end-point, population-based methods like polymerase chain reaction (PCR; for mRNA expression) or western blotting (for protein expression). These assays however, necessitate sample disruption for isolation of analytes. As such, it only provides a snapshot of the dynamic processes occurring (i.e. provides no temporal resolution). To this end, incorporation of reporter gene constructs enable continuous, longitudinal tracking of gene-of-interest’s expression profile. Nevertheless, it also has limitations including the tedious and lengthy development, and risks of introducing random mutations which make modified cells less clinically-friendly. In this thesis, application of nanosensor platform as a safe, non-integrative alternative for prolonged monitoring of cellular biomarkers is proposed and demonstrated. Specifically, nanosensors were fabricated by incorporating molecular beacons (MBs), oligonucleotide-based hairpin probes with specific target gene recognition ability, into biocompatible, biodegradable polymeric nanoparticles. Encapsulated within the nanocarriers, MBs can be effectively internalized by cells without requiring transfection procedures. Crucially, sustained release of MBs into the cytoplasmic region prolongs intracellular monitoring window of MBs, which are rapidly digested and cleared from cells otherwise. This was initially proven using MB targeted towards housekeeping gene of β-actin, against pore-inducing bolus MBs delivery method. Subsequently, nanosensor was applied to validate and track osteogenic (2D) and chondrogenic (3D hydrogel) differentiation of MSCs. In both cases, loading of nanosensors with both functional MBs (against specific differentiation markers) and reference MBs (against housekeeping gene), enable accurate depiction of cellular gene expression with good correlation against results from gold-standard of PCR (R2 value between 0.8 to 0.9). Finally, nanosensors were adapted to evaluate successful reprogramming induction of somatic fibroblast cells, relative to both PCR and gene-reporter validation. Aside from its monitoring performance, safety aspect of nanosensor labeling was studied in detail. Labeling concentration was assessed and optimized to ensure minimal influence over cell metabolism and proliferation rate. Meanwhile, multi-potency of labeled mesenchymal stem cells was minorly affected towards three differentiation lineages: adipogenesis, osteogenesis and chondrogenesis. At the same time, Oct4 protein expression and reprogramming efficacy were not impaired by nanosensor labeling. In conclusion, a facile, versatile yet safe nanosensor monitoring platform is introduced in this thesis. Especially for the field of regenerative medicine, such nanosensor can facilitate swifter translation of various therapeutic approaches by providing scientists information regarding dynamic cellular changes with both spatial and temporal resolution. In the future, such tool can be applied for optimization of culture conditions as well as purifying heterogenous cell populations to optimize treatment efficacy.